Forensic Psychiatry and Psychology in Europe A Cross-Border Study Guide (Springer International Publishing, 2018)
This study guide aims to make European trainees in forensic psychiatry and psychology and young forensic psychiatrists and psychologists aware of the differences and commonalities in forensic psychiatry and psychology in different countries within Europe and to enable them to learn from the approaches adopted in each country. The guide is divided into five main sections that address legal frameworks, service provision and frameworks, mandatory skills, teaching and training in forensic psychiatry and psychology, and capita selecta. In addition, recommendations are made with respect to the practice of teaching and training across European countries. It is anticipated that the guide will provide an excellent means of improving specific skills and that, by learning about the offender/patient pathways in the different jurisdictions of Europe, the reader will gain a deeper understanding of the principles that govern methods and practices in their own work with mentally disordered offenders.